A contemporary view of corporate finance theory, empirical evidence and practice. (November 2016) - Faff, Robert W; Gray, Stephen; Tan, Kelvin Jui Keng
This article uses a survey of Australian corporate treasurers to shed light on the gap between the theory and practice of corporate finance in Australia. Seven areas are examined: capital structure, payout policy, cash holdings, initial public offerings, seasoned equity offering, mergers and acquisitions, and corporate governance. We also exploit the global financial crisis (GFC) to examine the effect of liquidity shocks on a firm's capital structure choices. We then compare our Australian survey results with results from a comprehensive US survey conducted by Graham and Harvey. Our survey shows that the board of directors plays the most important role in determining capital structure decisions and that corporate treasurers play the most important role in cash holding decisions. This contrasts with the academic literature that has typically focused on the role of chief executive officer (CEO) in both capital structure and cash holding decisions. In addition, our respondents do not view the tax advantage of interest deductibility to be of first order of importance for debt issuance choices, which contrasts with most of the US empirical studies. Finally, we juxtapose the theory–practice perspective, with a review of the most recent 5 years (2011–2015) of corporate finance research published in the leading Asia Pacific Basin finance journals.